The Effect of Religiosity on Poor Adult Womanâ€™s Meaningfulness of Life - Muarifah, Alif; Muyana, Siti; Hidayah, Hudzaimah Nur (Islamic Guidance and Counseling Journal, 2020)
Having a meaningful life is a part of a happy, vigorous, anxiety-free life. Various factors, such as poverty and religiosity, may affect an individual's meaningfulness of life. Grounded from the phenomenon, the present study aims to find out the effect of poor adult womenâ€™s religiosity on the meaningfulness of life. The samples of the study were 123 women who were selected using cluster random sampling. The selected samples were women who met the criteria of â€œpoorâ€ according to the National Family Planning Coordination Board of the Republic of Indonesia (BKKBN RI), which is categorized as prosperous family 1. This study used meaningfulness of life scale and religiosity scale authors had developed. The data were analyzed using simple linear regression. The result showed that religiosity significantly affects the meaningfulness of life (F=55.659, p<0.005), meaning that the higher the religiosity, the higher the meaningfulness of life. The result of the study may provide a depiction of the effect of poor adult womanâ€™s religiosity on the meaningfulness of life, which can be used as a reference for the government or community observer on how to make a meaningful life by strengthening the religiosity.